Pengembangan Kewirausahaan Digital: Pendekatan Optimasi Bisnis Lokal - Abdul Ghonisyah, Ghaling Achmad; Barlian, Barin (Journal of Empowerment Community, 2023)
Indonesia is optimistic about becoming a developed country with a projected national entrepreneurship ratio of 3.9% in 2024. The government's strategic steps in encouraging institutions concerned with human development to work more progressively make it happen. The roles of higher education institutions in efforts to accelerate the achievement of the national entrepreneurship ratio through its tri dharma is also a responsibility that must be carried out sustainably. In community service, higher education creates entrepreneurial human resources relevant to science and technology development and can answer market problems or needs through the Digital Entrepreneurship Development Program. The science and technology that will be used in implementing the Digital Entrepreneurship Development Program is through the Local Business Optimization technology application platform. The method used in implementing the program is adapting the integrated learning initiatives approach, which includes masterclasses, action learning, peer-to-peer learning, and experiential workshops. After the participants took part in the integrated learning series, the program participants were able to determine a business model that suits their resources, whether to focus on the B2B scheme or the B2C scheme. However, this program will have more impact if its implementation receives support from partners who have the same program. Kata kunci: Kewirausahaan Digital, Transformasi Digital, Wirausaha Baru.